Efeito de vestes terapêuticas na funcionalidade de crianças com paralisia cerebral - Kennea Martins Almeida (2016)
Introduction: therapeutic suits, associated or not with intensive treatment protocols, have gained popularity in the rehabilitation of children with cerebral palsy (CP). Such garments are dynamic orthotics, which can contribute to better joint alignment while allowing movement. The growing interest in the use of these garments in clinical practice has stimulated scientific research to test the effects of each of the models available in promoting functionality of children with different PC clinical types. Objectives: The objectives of this thesis were: 1) analyzing and synthesizing available evidence on the effects of interventions that use therapeutic garments at treatment of functional limitations and disabilities of children with CP; 2) investigate the immediate effects of TheraSuit in postural alignment of lower limb in the sagittal plane and gait kinematics of children with CP. Methods: Two studies were carried out, namely: Study 1. systematic review study in which three independent reviewers have searched for experimental studies in MEDLINE, SciELO, BIREME, LILACS, PEDro and COCHRANE, between October and December/2015. Examiners assessed the methodological quality of selected studies with the Checklist for Measuring Quality. In order to synthesize the quality of evidence and strength of recommendation, the Grading of Recommendations Assessment, Development and Evaluation (GRADE) was used; Study 2. quasi-experimental study. The immediate effects of TheraSuit in postural alignment of lower limbs and gait kinematics (i.e., spatial-temporal variables and joint angles of lower limbs during the cycle gait) in children with diplegic CP, with crouch gait. The same group was evaluated under the conditions with the suit or without the suit. The garment´s elastic cords were adjusted in order to increase the extension of the hip and knee and the plantar flexion. For assessment of postural alignment and gait kinematics was used Tech MCS (Technaid) motion capture system, with four inertial measurement units (triaxial accelerometers, gyroscopes and magnetometers), fixed at the pelvis and lower limb (LL) of each child. Statistical analysis was performed using paired t-test (Bonferroni correction for multiple comparison resulted in á = 0.002). Results: Among 13 articles included in systematic review: two evaluated effects of full body suit (FBS), two evaluated effects of the Dynamic Elastomeric Fabric orthoses (DEFO), three evaluated effects of the TheraTogs and six evaluated effects of TheraSuit/AdeliSuit protocols. Referring to the quality of evidence, FBS, DEFO and TheraSuit/AdeliSuit protocols results were considered too low to structure and body unction outcomes, while the TheraTogs results were considered low. In the activity outcome, FBS, DEFO and TheraSuit showed very low quality and TheraSuit/AdeliSuit protocols and TheraTogs were low. Durint the quasi-experimental study 12 diplegic CP, crouch gait, 4-16 years old, GMFCS I-II children participated. The results showed no significant difference in postural alignment of the hip, knee and ankle in the sagittal plane, in orthostatic position, between the conditions with or without suit (p>0.002). There was significant difference among the investigated conditions, unfavorable to the condition with suit, in the following kinematic variables: walking speed (p<0.001), stride length (p=0.002) and range of motion (ROM) of the hip in the sagittal plane (p=0.001). There was no significant difference on the other gait kinematic variables, namely: hip ROM frontal plane, knee and ankle ROM sagittal plane, peaks of extension, adduction, abduction, internal and external rotation of the hip, flexion and extension peaks of the knee in phase support and peaks of dorsiflexion and plantar flexion of the ankle in the stance phase, (p> 0.002). Conclusion: Based on available literature, there are little evidence of positive effects brought by the four models of garments, FBS, TheraTogs, DEFO and TheraSuit/AdeliSuit, in the functionality of children with CP. The low quality of evidence in investigations related to the use of therapeutic suits suggests caution on the recommendation of this modality. The effects of immediate use of the TheraSuit seem to have restricted the movement of the hips of children with crouch gait, reducing the stride length and walking speed.